Genome-wide analysis of the homeodomain-leucine zipper family in Lotus japonicus and the overexpression of LjHDZ7 in Arabidopsis for salt tolerance - Wang, Dan; Gong, Yuan; Li, Yang; Nie, Shuming (Frontiers in Plant Science, 2022)
The homeodomain-leucine zipper (HD-Zip) family participates in plant growth, development, and stress responses. Here, 40 HD-Zip transcription factors of Lotus japonicus were identified and gave an overview of the phylogeny and gene structures. The expression pattern of these candidate genes was determined in different organs and their response to abiotic stresses, including cold, heat, polyethylene glycol and salinity. The expression of the LjHDZ7 was strongly induced by abiotic stress, especially salt stress. Subsequently, LjHDZ7 gene was overexpressed in Arabidopsis. The transgenic plants grew obviously better than Col-0 plants under salt stress. Furthermore, LjHDZ7 transgenic lines accumulated higher proline contents and showed lower electrolyte leakage and MDA contents than Col-0 plants under salt stress. Antioxidant activities of the LjHDZ7 overexpression lines leaf were significantly higher than those of the Col-0 plants under salt stress. The concentration of Na+ ion in LjHDZ7 overexpression lines was significantly lower than that of Col-0 in leaf and root parts. The concentration of K+ ion in LjHDZ7 overexpression lines was significantly higher than that of Col-0 in the leaf parts. Therefore, these results showed that overexpression of LjHDZ7 increased resistance to salt stress in transgenic Arabidopsis plants, and certain genes of this family can be used as valuable tools for improving abiotic stresses.